Somaclonal variation induction of Bogor taro (Colocasia esculenta) by gamma irradiation - FEBI NURILMALA; RICSON PEMIMPIN HUTAGAOL; IGA MANIK WIDHYASTINI; UTUT WIDYASTUTI; SUHARSONO SUHARSONO (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Nurilmala F, Hutagaol RP, Widhyastini IM, Widyastuti U, Suharsono.2017. Somaclonal variation induction of Bogor taro (Colocasia esculenta) by gamma irradiation. Biodiversitas 18: 28-33. Taro (Colocasia esculenta (L.) Schott) is a staple food that all parts of the plants can be consumed from the leaves, stems and corms. In the framework of breeding, diversity of characters has needed and somaclonal variation induction is the one of the utilized technological option. This research aims to develop somaclonal variation of Bogor taro to expand the diversity of character that leads to a new genotype which will then be multiplicated in order to meet the needs of superior seeds. Induction made to the apical shoots culture of Bogor taro with gamma ray irradiation doses of 0, 5, 10, 15, and 20 Gy. Evaluation of the mutants were conducted with AFLP markers and quantitative similarity analysis using UPGMA method. The results show that the gamma ray give influence on the number of leaves and the highest at doses of 10 Gy, not so on the new shoots and dose 20 Gy is a lethal dose. AFLP analysis of the 13 samples taro Bogor generate 235 fragments in the size of 50-255 bp and produces a dendogram with similarity coefficients 0.49 to 0.81 that the induction of somaclonal variation produces a diversity of up to 51% compared to the parent.Keywords: AFLP analysis, Colocasia esculenta, gamma ray irradiation, somaclonal variations, taroÂ